Review of Saint-Denis: A Town in the Middle Ages [Website] - Stephen Murray (Internet Archaeology, 2011)
How many of us, in teaching the history of medieval urbanism, or of Gothic architecture, have lamented the all-encompassing spread of suburbs and spaghetti highways that have obliterated the shape of the medieval city with its clearly defined walls and monastic bourgs? In the 1970s, Saint-Denis was a dreary smoke-blackened industrial suburb to the north of Paris, difficult to get to from downtown, and even dangerous for the unwary visitor. The glorious history of the site was represented only by the presence of the great abbey church (now a cathedral).